NasDem Party's Political Branding Strategy Through Anies Baswedan's Figure in Increasing Electability in the 2024 Karawang Legislative Election - Habibie Adzzikri; Jerry Indrawan (Journal of Governance and Social Policy, 2026)
The aim of this research is to find out how the Nasdem party's political branding strategy through the figure of Anies Baswedan is in increasing electability in the Karawang legislative election in 2024. This research uses Pich and Newman's political branding theory with a descriptive qualitative approach through interviews with the Karawang NasDem Party, the Election Supervisory Board, and political observers. The research results show that all aspects of the NasDem Party's political branding are directed at utilizing the figure of Anies Baswedan, thereby forming clear differentiation and a high level of voter identification. This strong connection has implications for the emergence of the coattail effect phenomenon, namely the alignment of voter preferences from the executive to electoral support for the legislative party. Overall, the NasDem Party's political branding strategy through the figure of Anies Baswedan had a significant influence on the NasDem Party's vote acquisition from 2 seats in the 2019 Election to 7 seats in the Karawang Election in 2024. However, this success really depends on collaboration between the party, the winning team and its legislative candidates. Nasdem needs to strengthen the party's identity and prove sustainable legislative performance to maintain voter loyalty in facing the upcoming elections.